Comparison of antigen uptake by peritoneal macrophages and veiled cells from the thoracic duct using isotope-, FITC-, or gold-labelled antigen. - Rhodes, J M (1989)
Veiled cells (VC), isolated from the thoracic duct of irradiated lymphadenectomized mice (MLNX) or peritoneal macrophages (PM phi were incubated with isotope-labelled hen egg lysozyme (HEL), purified protein derivative (PPD) or keyhole limpet haemocyanin (KLH) in vitro. About 2-10 times less antigen was associated with VC than with PM phi when measured in a Philips well-type scintillation counter. Autoradiographs of these cells indicated that 3-10% veiled cells had silver grains associated with them in contrast to 20-95% of the PM phi, depending on the type of antigen studied. It was also shown, from the distribution curves for grains in individual cells, that VC contained smaller numbers of grains than PM phi. Transmission electron microscopy using KLH conjugated with colloidal gold and immunofluorescence microscopy using KLH-FITC confirmed the results obtained from autoradiographs. However, measurements of the uptake of KLH-FITC by individual VC and PM phi using flow cytometry indicated that antigen was associated with nearly all VC in vitro but in much smaller amounts than with PM phi. Both VC and PM phi were capable of presenting HEL to primed T lymphocytes in vitro. These results are discussed in relation to the function of VC as accessory cells compared with PM phi.